Pengaruh Penerapan Good School Governance Terhadap Efektifitas Pengelolaan Dana Bantuan Operasional Sekolah di Surabaya - Kurnia Ulfah Fadhilah; Ade Irma Suryani Lating; Alphasyah Sidarta; Sulthon Falih Rasyid Rabbani (LPPM UBP, 2023)
This study aims to test the impact of implementing Good School Governance on the effectiveness of school operational assistance fund management, focusing on SDI Wachid Hasyim Rungkut Kidul, Surabaya. The research method used is a quantitative research approach with a causal associative method, gathering primary data through questionnaires completed by 90 respondents as the research sample, selected using a method called disproportionate random sampling. In this study, a multiple linear regression analysis is performed using SPSS version 23 software to determine the partial influence of the 6 principles of Good School Governance on the effectiveness of School Operational Assistance Fund (BOS) management. The study's findings show that, individually, the principles of Transparency, Accountability, Independence, Fairness, Participation, and Consensus Orientation do not have a significant impact on the effectiveness of School Operational Assistance Fund (BOS) management.